Respuesta :

assumption: y=kx then sustitude y=6,x=72 into y=kx
then 12y=x

Answer:

For the case when x = 8, we have that y = 2/3.

Step-by-step explanation:

The idea that y varies directly as x, can be written in an equation as:

y = k*x, where k is an unknown constant (until now).

We know that y=6 when x=72, then, substituting these values in the above formula gives us the value of k:

6 = k*72, then: k = 6/72 = 1/12.

Now, we can rewrite our initial expression with the known value of k as:

y = (1/12)*x

For the case when x = 8, we have that:

y = (1/12)*8 = 8/12 = 2/3.